Strategies Used by Islamic Religious Education Teachers to Instill Multicultural Values at Darut Taqwa Sooko Wringinanom Gresik, a Topranked Junior High School - Umar Faruq; Mochammad Faiz Sholichin; Moch. Nasir; M. Anang Sholikhudin (Ridwan Institute, 2026)
This study aims to analyze the strategies of Islamic Religious Education (PAI) teachers in instilling multicultural values at SMP Favorit Darut Taqwa Sooko Wringinanom Gresik. The background of this research is based on Indonesia’s multicultural society and the importance of education in fostering tolerance, mutual respect, and harmonious living within diversity. This study employs a qualitative approach with a descriptive research type using a case study design. Data were collected through observation, interviews, and documentation, with primary sources including PAI teachers and students. The findings reveal that teachers implement multicultural values through structured lesson planning, dialogical teaching methods, discussions, role modeling, and habituation of inclusive attitudes in both curricular and extracurricular activities. Additionally, teachers integrate values such as respect, open-mindedness, and cooperation into the learning process. The implementation of these strategies has proven effective in shaping students’ attitudes toward tolerance, respect for diversity, and social awareness in daily life. This research contributes to the development of multicultural-based Islamic education as an effort to build inclusive and harmonious student character in diverse societies.